Elachistelmis gen. n. (Coleoptera: Elmidae: Elminae) from Suriname, with description of two new species - Maier, Crystal A. (Zootaxa, 2012)
Elachistelmis gen. n. is described for two new species of riffle beetle, E. tetramera sp. n., and E. sipaliwiniensis sp. n. from southwestern Suriname. This new genus can be distinguished from all other elmid genera by its small size (ca. 1.0–1.2 mm), pronotum with sublateral carinae and lacking depressions, and the presence of a narrow band of plastron setae on the lateral edge of each elytron. Elachistelmis tetramera sp. n. is among the smallest recorded Elmini and possesses many characters associated with miniaturization, such as reduced tarsal formula and feathery wings with reduced venation. A key to species, scanning electron micrographs, and illustrations of the male genitalia are provided.